Simultaneous replacement of the aortic valve and hip joint in a patient with critical aortic stenosis and femoral neck fracture - S. V. Petrov; A. S. Peleshok; V. L. Ignatenko; O. M. Mutalibov; V. A. Krivopalov; G. G. Khubulava; N. G. Pilyugov (Вестник хирургии имени И.И. Грекова)
Concomitant cardiovascular diseases in elderly patients with a hip fracture significantly increase the risk of developing postoperative complications. Developing the treatment algorithm for a combination of two or more diseases in this category of patients is the main task. The advantages of simultaneous surgery are one-stage repair of two or more surgical diseases, the implementation of one anesthetic procedure, the reduction in the total time of the patient’s stay in the hospital and the reduction in rehabilitation time. This paper presents the clinical observation of simultaneous surgical treatment of severe aortic stenosis and femoral neck fracture in an elderly patient.